LEARNING LANGUAGE AS A LINGUISTIC SCIENCE - Saydaliyeva, Dilfuza (Журнал иностранных языков и лингвистики, 2023)
Our article provides insights into the theory previously explored in the field of linguistics. To a certain extent, connections are made between the general linguistic foundations and language-specific questions, theoretical knowledge is applied in practice. The field of linguistics can be divided into three binaries: synchronic and diachronic, theoretical and practical, and micro linguistics. From a micro linguistic perspective, languages ​​must be analyzed in their own right, without considering their social functions, how they are assimilated by children, the psychological mechanisms underlying the production and adoption of the language, and the literary and aesthetic or communicative functions of language.